Exploratory study of tolerability and immunological effect of a short up‐dosing immunotherapy phase with a standardised allergen extract derived from pollen of Olea europaea. Issue 1 (24th July 2015) - Moreno, Carmen; De San Pedro, Blanca Sáenz; Millán, Carmen; Panizo, Carmen; Martín, Santiago; Florido, Fernando
Abstract: Background: A new subcutaneous specific immunotherapy (SCIT) product adsorbed on aluminium hydroxide has been developed with a short and simplified up‐dosing phase, containing a biologically standardized allergen pollen extract from Olea europaea . Objective: To assess the tolerability profile of the updosing phase and its immunological effect, in terms of specific IgG4 and IgE levels and immediate skin reactivity. Material and methods: The study was an exploratory, multi‐centre, open‐label, single‐arm, phase II/III clinical trial. Adults with a clinical history of allergic rhinoconjunctivitis with/without asthma due to sensitization to olive pollen were selected. Five up‐dosing doses (300, 600, 3000, 6000 and 15000SQ+) were administered at weekly intervals, followed by a maintenance dose (15000SQ+) after 2 weeks. Adverse events were collected during the 30 min observation period after injections, after a telephone contact 2 days after each visit, and after reviewing the subjects' diary. IgG4 and IgE levels and immediate skin reactivity were evaluated at the beginning and at the end of the trial. Results: Ninety‐three subjects were included in the trial (mean age, 35.7 ± 10.3 years; women, 66.7 %). A total of 95 adverse drug reactions, all mild in intensity and non‐serious, were reported during the trial: 85 local in 34.4 % subjects, 9 systemic in 4.3 % subjects and one non‐specific (grade 0). Within 6 weeks, significant changes in IgG4 and IgE levels and in immediate skin reactivity to Olea europaea were accomplished. Conclusion: This new SCIT derived from pollen of Olea europaea presented a good tolerability profile and induced significant immunological responses already after a 6 week treatment. However, the non‐controlled design may limit the interpretation of these results. Trial registration: EudraCT no: 2011‐004852‐20; ClinicalTrials.gov Identifier: NCT01674595 .